Militant Islam reaches America - Pipes, Daniel, 1949- (New York : W.W. Norton, 2002)
An examination of militant Islam discusses its key features, outlines its differences from traditional Islam, looks at the threat it poses worldwide, and explains what steps must be taken to weaken the movement
مكتبة الشيخ صالح بن عبدا لله المالك [أمين مجلس الشورى السابق
Includes bibliographical references and index
1
Keywords: Islam and politics -- United States; Muslims -- Political activity -- United States; Slave trade -- Africa; United States -- Politics and government